Navigating Regulatory Landscapes: A Comprehensive Exploration of New Drug Approval Dossiers in the Complex Markets of the US, EU, and India - P. V V Siva Krishna; P. Srinivasa Babu; Ch. V Prasad Rao; M. Keerthi; O. Kousalya; A. Maheswar Reddy; K. Chaitanya Kumari; T. V Sai Manikanta (Journal for ReAttach Therapy and Developmental Diversities, 2023)
The Pharmaceutical Regulatory Affairs (PRA) division plays a crucial role within a pharmaceutical company by effectively steering the company's Research and Development (R&D) initiatives towards market success. In the current context, various countries possess distinct regulatory prerequisites for granting approval to a novel pharmaceutical product. Creating a cohesive regulatory plan for the submission of a new drug product's marketing authorization application (MAA), which could be applied across multiple countries through a single dossier, presents significant challenges. Therefore, the knowledge of exact and detailed regulatory requirements for MAA of each country should be known to establish a suitable regulatory strategy. The creation of the Common Technical Document (CTD) was driven by the goal of establishing a uniform template for technical documentation, streamlining the process of compiling registration applications for human pharmaceuticals. This standardization also aimed to simplify the preparation of electronic submissions while reducing the associated time and resource requirements. The development of a novel pharmaceutical necessitates extensive research across multiple domains, including chemistry, manufacturing practices, quality controls, preclinical sciences, and rigorous clinical trials. Regulatory agencies worldwide assign the task of assessing the research data to drug reviewers, who determine whether they substantiate the public health-serving attributes of safety, efficacy, and quality control for new pharmaceutical products. Each nation maintains an independent regulatory body tasked with enforcing rules and regulations, as well as issuing guidelines to oversee the marketing of pharmaceuticals. This work focuses on drug approval process and new drug applications in different countries like USA, Europe and India